Videogames, an alternative for learning - Reyes Alvarado , William Miguel; Fonseca Canaria, Edwin Arley; Rodríguez-Hernández, Karen Dayana (I+ T+ C- Research, Technology and Science, 2020)
The academic program of Licenciatura en Informática y Tecnología of the Universidad Pedagógica y Tecnológica de Colombia (UPTC) is ahead of the project Limits and Outcomes of Gamification in the Field of the Teaching-Learning Relationship of the Degree in Computer Science and Technology of the UPTC, as part Of the purposes of the GIACE seedling group; The general objective proposed for this research is to establish the limits and the scope of the theoretical assumptions involved in the gamification in order to recognize its implementation in the field of teaching-learning relationship in the Degree in Computer Science and Technology of the UPTC. As part of the progress made, this paper presents a theoretical tracking centered on those studies that pose to videogames as a learning tool. Within the results it is emphasized that the forms and techniques used for the creation of a video game and, in turn, play it, is an art. It is also pertinent to say that video games are not harmful to mental and physical health, as long as the person who plays, does not exceed the recommended maximum times, nor obsess with this activity, so that the time spent playing is not A factor that influences the performance of their school life, nor affect their social and emotional life.